Goethe in the Shadow of the East: the Influence of the Quran on West- Eastern Divan - Mostafa Hosseini (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
AbstractThere is a close relationship between Comparative Literature and Translation Studies, especially in the domain of influence studies. The famous German poet, novelist and dramatist, Johann Wolfgang von Goethe, from his early youth was somehow interested to the East, in the inclusive sense of the word, and regularly read the books, in different European national languages, on East and its people. While reading these miscellaneous books that he became acquainted with Muslims’ religious book, the Holy Quran, and greatly was influenced by it. This impact is quite conspicuous, notably, in his most comprehensive book of poetry, West- Eastern Divan (1819). The present paper tries, through the prism of Comparative Literature especially influence studies, to investigate historical and personal evidences. At the beginning Goethe’s familiarity with the Quran and its translations which he read are elaborated on. Later on, the twelve books of West- Eastern Divan and its long epilogue, Notes and Papers Written for a Better Understanding of Divan, are analyzed very precisely, and Goethe’s sources of inspiration are, one by one, identified and explained.